Strategies to Increase Discipline in Distance Learning - Estiyani, Septi Wahyu; Mahmudah, Fitri Nur (Universitas Pendidikan Ganesha, 2021)
The distance learning process carried out by teachers and students is a challenge, especially related to learning motivation and student learning discipline. This study analyzes strengthening learning to improve student learning discipline during the pandemic. The method used in this research is qualitative with a case study approach. The research procedure uses Miles and Huberman. Data collection techniques using observation and interviews. Data analysis was carried out using Atlas.ti software version 8. The results of this study indicate the importance of student response, strengthening parents' motivation, and student learning focus. Some of the research results related to three important focuses: strategies to improve learning, respond to improvements, and distance learning. Based on the study results, it can be seen that children in the distance learning process very much need parents during a pandemic like now. Parents must also be able to discipline their children during learning activities. To discipline children, parents encourage children to be more enthusiastic in learning. Reinforcement provided by parents is to strengthen verbally and some are in the form of nonverbal.